2009
DOI: 10.1142/s0219891609001940
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric-Hyperbolic Equations of Motion for a Hyperelastic Material

Abstract: Abstract. We offer an alternate derivation for the symmetric-hyperbolic formulation of the equations of motion for a hyperelastic material with polyconvex stored energy. The derivation makes it clear that the expanded system is equivalent, for weak solutions, to the original system. We consider motions with variable as well as constant temperature. In addition, we present equivalent Eulerian equations of motion, which are also symmetric-hyperbolic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 20 publications
(24 reference statements)
0
26
0
Order By: Relevance
“…It has been shown that the enhanced p-F -J formulation overcomes locking and non-physical hydrostatic fluctuations in the pressure, providing a good balance between accuracy and speed of computation. The incorporation of polyconvex energy functionals [81,82] into the existing mixed methodology is the next step of our work.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the enhanced p-F -J formulation overcomes locking and non-physical hydrostatic fluctuations in the pressure, providing a good balance between accuracy and speed of computation. The incorporation of polyconvex energy functionals [81,82] into the existing mixed methodology is the next step of our work.…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, the strain energy Ψ per unit undeformed volume must be a function of the deformation gradient F via a convex multi-valued function W [62] as:…”
Section: Constitutive Laws: Polyconvex Elasticitymentioning
confidence: 99%
“…The three strain measures F , H and J have work conjugate stresses Σ F , Σ H and Σ J defined by [45,46,62,63]:…”
Section: Constitutive Laws: Polyconvex Elasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, following Gil and Ortigosa [1,2], we propose an extended Hu-Washizu [44,52,54,54,[69][70][71][71][72][73][74][75][76][77][78][79][80] mixed variational principle for nearly and truly incompressible scenarios. Considering now interpolation spaces which satisfy the LBB condition, a comparison of this enhanced methodology is carried out in this paper against the three-field formulation, where both LBB compliant and non-compliant interpolation spaces are considered.…”
Section: Introductionmentioning
confidence: 99%